Strategic responsiveness and Bowman's risk–return paradox - Andersen, Torben Juul; Denrell, Jerker; Bettis, Richard A. (Strategic Management Journal, 2007)
One of the most enduring puzzles in the strategy literature is the negative association between risk and return known as the Bowman paradox. This paper formalizes a model of strategic conduct based on the concept of strategic fit and the heterogeneity of firm strategic capabilities. This model is shown mathematically to yield the negative association of the Bowman paradox. Furthermore, the model makes several other testable predictions. To examine these predictions, simulated data from the model are compared with a large empirical study of 45 industries during 1991–2000. The predictions of the model are consistent with the empirical data. Copyright © 2007 John Wiley & Sons, Ltd.